The Effects of IFRS Convergence on Earnings Quality of Chinese Listed State-owned Enterprises - ZHANG, YI (2016)
This paper examines the effects of IFRS convergence on earnings quality of Chinese listed state-owned enterprises after controlling the effect of the split-share reform on earnings quality. 321 Chinese listed state-owned enterprises are selected and the sample period commences from 2004 to 2009. By the use of the Cross-sectional Modified Jones Model, the absolute value of discretionary accruals can be obtained and then can be used to measure earning management in Chinese listed state-owned enterprises. After applying the univariate test and the multivariate regression, the results show that there is an increase in earnings quality of Chinese listed state-owned enterprises in post-IFRS convergence period even after controlling the effect of the split-share reform on earnings quality.